The impact of storms and stratification on sediment transport in the Rhine region of freshwater influence. Issue 5 (31st May 2017) - Flores, Raúl P.; Rijnsburger, Sabine; Horner‐Devine, Alexander R.; Souza, Alejandro J.; Pietrzak, Julie D.
Abstract: We present measurements of along and across‐shore sediment transport in a region of the Dutch coast 10 km north of the Rhine River mouth. This section of the coast is characterized by strong vertical density stratification because it is within the midfield region of the Rhine region of freshwater influence, where processes typical of the far‐field, such as tidal straining, are modified by the passage of distinct freshwater lenses at the surface. The experiment captured two storms, and a wide range of wind, wave, tidal and stratification conditions. We focus primarily on the mechanisms leading to cross‐shore sediment flux at a mooring location in 12 m of water, which are responsible for the exchange of sediment between the nearshore and the inner shelf. Net transport during storms was directed offshore and influenced by cross‐shelf winds, while net transport during spring tides was determined by the mean state of stratification. Tidal straining dominated during neap tides; however, cross‐shore transport was negligible due to small sediment concentrations. The passage of freshwater lenses manifested as strong pulses of offshore transport primarily during spring tides. We observe that both barotropic and baroclinic processes are relevant for cross‐shore transport at depth and, since transport rates due to these competing processes were similar, the net transport direction will be determined by the frequency and sequencing of these modes of transport. Based on our observations, we find that wind and wave‐driven transport during storms tends move fine sediment offshore, while calmer, more stratified conditions move it back onshore. Plain Language Summary: This paper describes different mechanisms capable of exchanging sediments, contaminants and biological materials between shallow areas close to the shore and deep offshore areas, in a coastal region influenced by the freshwater discharge of a large river. In general, our results show that storms, with high winds and waves, move sediment offshore whereas calmer periods when the water column is stratified move sediment onshore. The total balance is defined by the frequency and sequencing of these modes of transport. Key Points: Net cross‐shore transport results from the combination of three transport mechanisms that turn on and off in response to the forcing conditions Barotropic transport at depth during storms results in net offshore transport. Baroclinic transport at depth during stratified periods results in onshore transport Tidal plume fronts manifest as strong pulses of seaward transport at depth, presenting a dynamical component not observed in the far‐field